Assessing Egypt’s Readiness to Introduce Program and Performance-Based Budgeting - Negm, Eman (AUC Knowledge Fountain, 2025)
Program and performance-based budgeting is one of the recent and most controversial developments in the Egyptian budgetary system. As a results-based budgeting methodology, it can potentially support the government's endeavors to enhance the efficiency and effectiveness of public expenditures and improve the overall levels of transparency and accountability. As per the new Unified Finance Law, Egypt is preparing for the full implementation of the program and performance budgeting reform to start in FY 2027-2028. The main objective of this study is to assess the readiness of Egypt to introduce program and performance-based budgeting based on six main assessment pillars which are: 1) Data Availability and Reliability, 2) Capacity Building and Organizational Culture, 3) Stakeholder Engagement and Political Will, 4) Institutional Reform, 5) Defining Performance (Effectiveness of Service Delivery): Monitoring and Evaluation Mechanisms, and 6) Accountability System and Incentives Schemes. The results of the conducted qualitative research showed that Egypt still has a long road to hit to become ready for the results-based budgetary reform. On the one hand, some important implementation prerequisites are mostly fulfilled, such as the development of the legislative framework and building the personnel capacities on basic program and performance budgeting principles. On the other hand, missing sectoral strategies, unreliable data sources, and misalignment with the organizational structures and restructuring efforts receive alarmingly less attention. The analysis showed that there are two main characteristics behind the current readiness situation of Egypt which are the cultural resistance to program and performance-based budgeting and the missing supporting structural set-up.